Inovasi Produk Berbasis Genjer (Limnocharis flava) untuk Pemberdayaan Ekonomi dan Sosial Masyarakat Desa Sukodono - Listyawati, Listyawati; Yudhanti, Ashari Lintang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study is motivated by the local potential of genjer (Limnocharis flava) in Sukodono Village, which has long been used in a limited way despite its broader economic opportunities. The research applied the Asset-Based Community Development (ABCD) approach, emphasizing the utilization of local assets as the foundation of empowerment. The stages included surveys and observations to map 18 plots of genjer, socialization to raise awareness of its nutritional and economic potential, training through cooking demonstrations to develop value-added products (genjer rempeyek and festive cookies), mentoring to strengthen technical and managerial aspects, and evaluation through market testing at the Muharam Bazaar. The results showed that genjer based innovations received positive acceptance with a sales rate of 87.5% and a recorded profit, despite the small-scale production. These findings confirm that innovations based on local assets can enhance the added value of local products while simultaneously strengthening community empowerment.